Expression of the Arabidopsis Mg-chelatase H subunit alleviates iron deficiency-induced stress in transgenic rice - Tran, Lien Hong; Kim, Jin-Gil; Jung, Sunyo (Frontiers in Plant Science, 2023)
The most common symptom of iron (Fe) deficiency in plants is leaf chlorosis caused by impairment of chlorophyll biosynthesis. Magnesium (Mg)-chelatase H subunit (CHLH) is a key component in both chlorophyll biosynthesis and plastid signaling, but its role in Fe deficiency is poorly understood. Heterologous expression of the Arabidopsis thaliana Mg-chelatase H subunit gene (AtCHLH) increased Mg-chelatase activity by up to 6-fold and abundance of its product, Mg-protoporphyrin IX (Mg-Proto IX), by 60–75% in transgenic rice (Oryza sativa) seedlings compared to wild-type (WT) controls. Noticeably, the transgenic seedlings showed alleviation of Fe deficiency symptoms, as evidenced by their less pronounced leaf chlorosis and lower declines in shoot growth, chlorophyll contents, and photosynthetic efficiency, as indicated by Fv/Fm and electron transport rate, compared to those in WT seedlings under Fe deficiency. Porphyrin metabolism was differentially regulated by Fe deficiency between WT and transgenic seedlings, particularly with a higher level of Mg-Proto IX in transgenic lines, showing that overexpression of AtCHLH reprograms porphyrin metabolism in transgenic rice. Leaves of Fe-deficient transgenic seedlings exhibited greater upregulation of deoxymugineic acid biosynthesis-related genes (i.e., NAS, NAS2, and NAAT1), YSL2 transporter gene, and Fe-related transcription factor genes IRO2 and IDEF2 than those of WT, which may also partly contribute to alleviating Fe deficiency. Although AtCHLH was postulated to act as a receptor for abscisic acid (ABA), exogenous ABA did not alter the phenotypes of Fe-deficient WT or transgenic seedlings. Our study demonstrates that modulation of porphyrin biosynthesis through expression of AtCHLH in transgenic rice alleviates Fe deficiency-induced stress, suggesting a possible role for CHLH in Fe deficiency responses.